Sopesando al tercero registral versus el usucapiente: Un enfoque desde el sistema peruano - Santillán García, Patricia (Pontificia Universidad Católica del Perú, 2024)
This article analyses the ownership dispute arising from a third party acquiring a real estate from a person who appeared in the Public Records as the owner but without knowing that the real estate was owned by an adverse possessor. The autor approaches this phenomenon based on the provisions of the Peruvian Registry system and its particularities, critically analyzing various positions on this de facto assumption that have been outlined by various doctrines, to subsequently make a comprehensive interpretation of the existing regulations in our system to finally solve this dispute.

En el presente artículo se analiza el conflicto de propiedad que surge entre el tercero que adquiere un predio de quien aparecía en Registros Públicos como propietario sin tener conocimiento de que el inmueble le pertenecía en propiedad al usucapiente. La autora aborda este fenómeno a partir de las disposiciones del sistema registral peruano y sus peculiaridades, analizando de manera crítica las distintas posiciones sobre este supuesto de hecho que han esbozado diversos sectores de la doctrina, para luego exponer una interpretación en conjunto de las normas existentes en nuestro ordenamiento que resuelve en definitiva esta controversia.
Balancing registered third parties against adverse possessors: Approach from the Peruvian registry system
Keywords: Adverse possession; Usucaption against registered owner; Registered third party; Principle of registration public faith; Property conflict; Real estate; Real rights; Articles 952 and 2014 of the Civil Code; Prescripción adquisitiva de dominio; Usucapión contra tabulas; Tercero registral; Principio de fe pública registral; Conflicto de propiedad; Propiedad inmueble; Derechos reales; Artículos 952° y 2014° del Código Civil; https://purl.org/pe-repo/ocde/ford#5.05.00